2020
DOI: 10.1017/s0022029920000990
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor α participates in LPS-induced reduction of triglyceride synthesis in bovine mammary epithelial cells

Abstract: Lipopolysaccharides (LPS) could induce milk fat depression via regulating the body and blood fat metabolism. However, it is not completely clear how LPS might regulate triglyceride synthesis in dairy cow mammary epithelial cells (DCMECs). DCMECs were isolated and purified from dairy cow mammary tissue and treated with LPS. The level of triglyceride synthesis, the expression and activity of the liver X receptor α (LXRα), enzymes related to de novo fatty acid synthesis, and the expression of the fatty acid trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…2A †). Some studies found that LPS intervention inhibited TG synthesis and secretion in bovine mammary epithelial cells (DCMECs), 46,47 while other studies found that 4-week LPS (300 μg kg −1 d −1 ) infusion increased liver TG contents in C57BL/6J mice, 48 and intraperitoneal injection of LPS in mice accelerated hepatic fat accumulation. 49 This scientific question needs to be further explored.…”
Section: Papermentioning
confidence: 99%
“…2A †). Some studies found that LPS intervention inhibited TG synthesis and secretion in bovine mammary epithelial cells (DCMECs), 46,47 while other studies found that 4-week LPS (300 μg kg −1 d −1 ) infusion increased liver TG contents in C57BL/6J mice, 48 and intraperitoneal injection of LPS in mice accelerated hepatic fat accumulation. 49 This scientific question needs to be further explored.…”
Section: Papermentioning
confidence: 99%